The perpetual state of emergency that sacrifices protected areas in a changing climate - Twidwell, Dirac; Wonkka, Carissa L.; Bielski, Christine H.; Allen, Craig R.; Angeler, David G.; Drozda, Jacob; Garmestani, Ahjond S.; Johnson, Julia; Powell, Larkin A.; Roberts, Caleb P. (Conservation biology, 2018)
A modern challenge for conservation biology is to assess the consequences of policies that adhere to assumptions of stationarity (e.g., historic norms) in an era of global environmental change. Such policies may result in unexpected and surprising levels of mitigation given future climate-change trajectories, especially as agriculture looks to protected areas to buffer against production losses during periods of environmental extremes. We assessed the potential impact of climate-change scenarios on the rates at which grasslands enrolled in the Conservation Reserve Program (CRP) are authorized for emergency harvesting (i.e., biomass removal) for agricultural use, which can occur when precipitation for the previous 4 months is below 40% of the normal or historical mean precipitation for that 4-month period. We developed and analyzed scenarios under the condition that policy will continue to operate under assumptions of stationarity, thereby authorizing emergency biomass harvesting solely as a function of precipitation departure from historic norms. Model projections showed the historical likelihood of authorizing emergency biomass harvesting in any given year in the northern Great Plains was 33-28% based on longterm weather records. Emergency biomass harvesting became the norm (>50% of years) in the scenario that reflected continued increases in emissions and a decrease in growing-season precipitation, and areas in the Great Plains with higher historical mean annual rainfall were disproportionately affected and were subject to a greater increase in emergency biomass removal. Emergency biomass harvesting decreased only in the scenario with rapid reductions in emissions. Our scenario-impact analysis indicated that biomass from lands enrolled in the CRP would be used primarily as a buffer for agriculture in an era of climatic change unless policy guidelines are adapted or climate-change projections significantly depart from the current consensus. Un reto moderno para la biología de la conservación es la evaluación de las consecuencias de las políticas que se adhieren a las suposiciones de inmovilidad (p. ej.: las normas históricas) en una era de cambio ambiental global Dichas políticas pueden resultar en niveles inesperados y sorprendentes de mitigación dadas las futuras trayectorias del cambio climático，especialmente cuando la agricultura se fija en las áreas protegidas para amortiguar las pérdidas de producción durante los periodos de extremos ambientales. Evaluamos el impacto potencial de los escenarios de cambio climático sobre las tasas a las que los pastizales enlistados en el Programa de Reservas para Conservación (CPR，en inglés) están autorizados para cosechas de uso agrícola por emergencia (es decir，extracción de biomasa)，lo que puede ocurrir cuando la precipitación de los cuatro meses previos está por debajo del 40% de la precipitación media normal o histórica para ese periodo de cuatro meses. Desarrollamos y analizamos escenarios bajo la condición que las políticas continuarán operando bajo suposiciones de inmovilidad, autorizando así la cosecha de biomasa solamente como función de la separación entre la precipitación y las normas históricas. Las proyecciones de los modelos mostraron que la probabilidad histórica de la autorización de cosechas de biomasa por emergencia en cualquier año dado en la parte norte de las Grandes Planicies fue de 33.28% con base en registros climáticos de largo plazo. La cosecha de biomasa por emergencia se convirtió en la norma (>50% de los años) en el escenario que reflejó incrementos continuos en las emisiones y una disminución en la precipitación durante las temporadas de crecimiento，y las áreas en las Grandes Planicies con una precipitación media anual más alta históricamente estuvieron afectadas desproporcionalmente y estuvieron sujetas a un incremento mayor en la extracción de biomasa por emergencia. La cosecha de biomasa por emergencia disminuyó solamente en el escenario con las reducciones rápidas en las emisiones. Nuestro análisis de impacto de escenarios indicó que la biomasa de los terrenos enlistados en el CRP se usaría principalmente como amortiguador para la agricultura en una era de cambio climático a menos que las pautas políticas se adapten o las proyecciones del cambio climático se separen significativamente del consenso actual. 保护生物学目前面临的ー个挑战是评估在全球环境变化的时代背景下，遵循稳定性假设（如历史常态)的 政策可能的结果。考虑到未来的气候变化轨迹，这样的政策可能导致出人意料的减排水平，特別是农业生产还依 靠保护地来缓冲极端环境出现时的生产损失。我们评估了气候变化情景对纳入《土地休耕保护计划，CRP) 的 草地被授权用于农业用途的紧急采收（即生物质移除) 比例的潜在影响，当前 4 个月的降水量低于正常或历史上 这四个月的平均降水量的40%时可以得到授权。我们发展并分析了当政策仍继续遵循稳定性假说时的情景，这 样对紧急生物质采收的授权仅依据降水量对历史常态的偏离。模型预测表明，根据长期的天气记录，在任意一年 北美大平原北部被授权进行紧急生物质采收的历史可能性是33.28%。在排放量持续增长、生长期降水量下降 的情景下，紧急生物质采收将成为常态(超过50%的年份)，北美大平原上历史平均年降雨量较高的地区会不成 比例地受到影响，紧急生物质采收大大增加。只有在快速减排的情景下，紧急生物质采收会減少。我们的情景影 响分析表明，在气候变化的时代，納入CRP计划土地的生物质将主要被用于农业生产的缓冲，除非政策准则能够 作出相应的调整，或气候变化预测显著偏离当前的共识。翻译: 胡怡& •审校:親辅文